2017
DOI: 10.4236/oalib.1103493
|View full text |Cite
|
Sign up to set email alerts
|

A Deterministic Mathematical Model for Direct and Indirect Transmission Dynamics of Typhoid Fever

Abstract: Improvements in sanitation and the provision of clean drinking water led to the elimination of typhoid fever from developed countries in the beginning of the 20th century. However, Salmonella typhi and paratyphi remain a major source of morbidity and mortality in many developing countries today. The dynamics of typhoid transmission are poorly understood. In this study, we develop a novel mathematical model that captures the role of both human to human interaction and human to environment interaction in the tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 17 publications
(10 reference statements)
0
13
0
Order By: Relevance
“…Vaccination is an action of planting weakened germs into a human's body through scratching or injecting a needle so that the person becomes immune to the disease infection. This preventive action effectively reduces the risk of being infected in the human population [3,48]. Moreover, the authors [48] confirmed that an aggressive vaccination in 9-month, 6-year, and 12-year olds could reduce >85% the cases of typhoid by an 80% coverage.…”
Section: Systematic Literature Review Resultsmentioning
confidence: 79%
See 4 more Smart Citations
“…Vaccination is an action of planting weakened germs into a human's body through scratching or injecting a needle so that the person becomes immune to the disease infection. This preventive action effectively reduces the risk of being infected in the human population [3,48]. Moreover, the authors [48] confirmed that an aggressive vaccination in 9-month, 6-year, and 12-year olds could reduce >85% the cases of typhoid by an 80% coverage.…”
Section: Systematic Literature Review Resultsmentioning
confidence: 79%
“…The mathematical model for typhoid disease was developed by considering various interventions to control the disease and reduce infection risk. The intervention used most in controlling the disease is treatment [3,18,43,47,50,53,55,57]. Based on some research, treatment is confirmed as the best intervention in controlling the spread of typhoid disease.…”
Section: Systematic Literature Review Resultsmentioning
confidence: 99%
See 3 more Smart Citations